Buster Effect of Apricot Kernel Oil On Hypocholesteremia: Effect of Apricot Kernel Oil on Hypocholesteremia - Tabassum, Rafia; Farooq, Umar; Yousaf Quddoos, Muhammad; Anjum Murtaza, Mian; Sami Ullah, Tayyaba; Fatima, Ishrat; Fatima, Areeja; Rehman, Muhammad Anees Ur; Chaudhry, Faiqa; Kauser, Samina; Noreen, Saima; Qadeer, Zara; et al. (Pakistan Journal of Health Sciences, 2023)
Cholesterol is a natural substance produced by liver in human body According to research based on Framingham Heart Study, ideal cholesterol level is below than 150 mg/dL. Apricot (Prunus armeniaca) is an important medicinal plant belongs to family Rosaceae which is also grown in Pakistan. In local language it is called “Kubani” having nutritious flesh, pits containing kernels. Objective: To explore therapeutic potential of apricot kernel oil on hypercholesterolemic rabbits. Method: Apricot kernel oil was extracted by cold extraction method. Rabbits were adapted for two weeks before starting treatments. Total feed doses i.e. 250 g was divided in two portions and were given to rabbits in early morning and early evening. Food consumption for every rabbit was consistent to 250 g/day for four week’s experimentation. Results: After usage of 1 % apricot Kernel oil (supplemented) the maximum blood cholesterol level decreased from 159.38 mg/dL to 122.8 mg/dL and also decreased in blood triglyceride level was from 237.82 mg/ dL to 192.20 mg/ dL. The HDL contents of rabbits were increased from 26.750 mg/ dL to 33.450 mg/ dL. LDL contents of rabbits were decreases from 46.90 mg/ dL to 36.05 mg/ dL. VLDL contents of rabbits were decreases from 23.7 mg/ dL to 18.3 mg/ dL detected after Six weeks. Conclusion: Current study was carried out. Apricot kernel oil has ability to remove the lipid profile especially cholesterol